Lowering the cost of large-scale energy storage: high temperature adiabatic compressed air energy storage - Cárdenas, B.; Pimm, Andrew James; Kantharaj, Bharath; Simpson, M.C.; Garvey, J.A.; Garvey, Seamus D. (2017)
Compressed air energy storage is an energy storage technology with strong potential to play a significant role in balancing energy on transmission networks, owing to its use of mature technologies and low cost per unit of storage capacity. Adiabatic compressed air energy storage (A-CAES) systems typically compress air from ambient temperature in the charge phase and expand the air back to ambient temperature in the discharge phase. This papers explores the use of an innovative operating scheme for an A-CAES system aimed at lowering the total cost of the system for a given exergy storage capacity. The configuration proposed considers preheating of the air before compression which increases the fraction of the total exergy that is stored in the form of high-grade heat in comparison to existing designs in which the main exergy storage medium is the compressed air itself. Storing a high fraction of the total exergy as heat allows reducing the capacity of costly pressure stores in the system and replacing it with cheaper thermal energy stores. Additionally, a configuration that integrates a system based on the aforementioned concept with solar thermal power or low-medium grade waste heat is introduced and thoroughly discussed.